Oor die kortkuns van John Miles - De Beer, Marésa (Rhodes University, Faculty of Humanities, School of Languages, 1988)
This thesis involves intensive analyses of some of the short-short stories in John Miles's Liefs nie op straat nie, in order to reveal the narrative strategies employed in each. In other words, it is geared to "the rules that govern ... textual actualization and, consequently, those rules that govern the way literary discourse functions as communication" (Riffaterre 1983: 158). Subsequently, attention is given to the interrelationship among the texts, the way in which they act upon one another and interact with the title of the volume, in order to establish the function of such relations. The following texts are analysed in consecutive chapters: "Lucy", "Lappies, kan jy my hoor, Lappies?", "Voorgevoel", "Dom Nakkie, my Dom Nakkie" and "Wie het nog Dom Nakkie gesien?", "Hy staan by die deur en hy klop", "Gustav gaan speel", and "Liefs nie op straat nie". In a concluding chapter the implications of the title are discussed with reference to all the texts in the volume, including those not analysed individually. It is concluded that, on the one hand, the expectations raised by the title are ironicized because the title is never "completed" explicitly, and because that which, by implication, should not be seen in public ("op straat"), is specifically situated in the street and scrutinized in close-up. But on the other hand the title also evokes a peculiar mentality present in all the texts, either in the narrators, or in the characters, or in both. The discussion of "Lucy" is focussed mainly on the contrast and interaction between the world of the child and that of the adult and on the way in which this interaction is actualized within the text through the contrast in the experience of time, the use of "mémoire involontaire", "durée" and the contrasts between (and overlapping of) narrative perspective and focalization. In respect of "Lappies, kan jy my hoor, Lappies?" special attention is paid to similarities and contrasts between this text and the traditional suspense story, notably the way in which conventional techniques are employed to create suspense, as well as to generate an entire subtext which eventually "relocates" the text on the niveau of the murderer's psychological dilemma. In discussing "Voorgevoel" emphasis is not placed primarily on what is conveyed by the narrator, but on the way in which his intentions are subverted both by the window pane through which he is looking and by the narration as such. In this way he is foregrounded and revealed as narrator, just as the text is foregrounded and revealed as literature, with the emphasis, in both cases, not only on their defence mechanisms but also on their impotence. "Dom Nakkie, my Dom Nakkie" and "Wie het nog Dom Nakkie gesien?" are grouped together in one chapter in order to illuminate the interaction between the two narratives in the first text, as well as the interaction between the two texts. Ultimately, they may be seen as three narratives juxtaposed through irony and relativism. The "triumph" of the "preferably not in public" mentality, both in the text and in society, is also illustrated by the interaction between the three narratives. In chapter, 5, in which "Hy staan by die deur en hy klop" is discussed, attention is focussed on the ironic function of the Biblical references, the contrast between Jan and the rest of society, and the way in which the "climax" is located within the Iserian "blank" in the text, so that the entire process of decoding is based on a filling in of that "blank" and its implications. "Gustav gaan speel" is based loosely on Barthes's lexia model, in order to determine the signifying process in the text, and also to demonstrate the way in which the text presupposes rereading. In the discussion of the title text it is revealed how the text is centered in the basic dichotomy between the narrator-as-writer and the journalist, and the way in which this polarity is relativized by the text as such. The text is demonstrated to be the credo of the volume as a whole as well as of the fiction of the Seventies in Afrikaans.
Keywords: Miles, John, 1938- -- Criticism and interpretation